2019
DOI: 10.1002/1878-0261.12410
|View full text |Cite
|
Sign up to set email alerts
|

Protein profiling of fine‐needle aspirates reveals subtype‐associated immune signatures and involvement of chemokines in breast cancer

Abstract: There are increasing demands for informative cancer biomarkers, accessible via minimally invasive procedures, both for initial diagnostics and for follow‐up of personalized cancer therapy, including immunotherapy. Fine‐needle aspiration (FNA) biopsy provides ready access to relevant tissue samples; however, the minute amounts of sample require sensitive multiplex molecular analysis to be of clinical biomarker utility. We have applied proximity extension assays (PEA) to analyze 167 proteins in FNA samples from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 35 publications
3
22
0
Order By: Relevance
“…This expression pattern is very similar to the pattern earlier obtained for tonsillar and base of tongue cancer analyzed with the same Proseek panel 27 . Also in a study on breast cancer, a similar expression pattern with upregulation of CCL2‐4 and 7‐8, CXCL 9‐11, and IL‐6 in cancer vs benign lesions was observed 30,31 . Notably, upregulation of CCL2‐4, 8, and CXCL9‐11 and 13 are all part of a 12‐chemokine gene expression signature associated with lymph node‐like structures in melanoma, colorectal cancer, breast cancer and melanoma, and proposed to indicate a potential for immune therapy 32‐34 .…”
Section: Discussionsupporting
confidence: 85%
“…This expression pattern is very similar to the pattern earlier obtained for tonsillar and base of tongue cancer analyzed with the same Proseek panel 27 . Also in a study on breast cancer, a similar expression pattern with upregulation of CCL2‐4 and 7‐8, CXCL 9‐11, and IL‐6 in cancer vs benign lesions was observed 30,31 . Notably, upregulation of CCL2‐4, 8, and CXCL9‐11 and 13 are all part of a 12‐chemokine gene expression signature associated with lymph node‐like structures in melanoma, colorectal cancer, breast cancer and melanoma, and proposed to indicate a potential for immune therapy 32‐34 .…”
Section: Discussionsupporting
confidence: 85%
“…49 Differential gene expression analysis of patient subgroups with good versus bad survival (based on 4 independent signatures of apoptotic proficiency) identified 11 genes similarly enriched in either of these groups, 8 of which had previously been attributed an impact on breast cancer progression or patient survival ( Figures 5 and 6). 34,[37][38][39][40][41][42][43] The expression levels of these genes also conveyed prognostic value in patients from the METABRIC dataset ( Figure 6 and Tables 1and 2), with the potential exception of CYP4X1. Of the remaining three genes, LTB failed to impact cancer-specific overall survival in the METABRIC cohort (Tables 1 and 2), while both CLIC6 and SLC7A2 were strongly associated with improved disease outcome ( Figure 6 and Tables 1 and 2), although only SLC7A2 as an independent prognostic biomarker ( Table 2).…”
Section: Discussionmentioning
confidence: 96%
“…Strikingly, 7 of these 11 genes have previously been attributed an impact on breast cancer progression and patient survival that is in line with our findings. These genes are AGR3, 34 ANKRD30A, 35 BMPR1B, 36,37 STC2 38,39 and SUSD3, 40 which are all indicators of early disease or good prognosis, as well as CXCL9, 41,42 and CALML5, 43 both of which have previously been linked to disease progression or poor prognosis. Conversely, CYP4X1 (which is our hands was enriched in patients with good survival) has previously been positively correlated with tumor grade.…”
Section: Signatures Of Apoptotic Proficiency Convey Negative Prognostmentioning
confidence: 99%
“…Chemokines are cytokines with a chemotactic behavior. They are widely studied in BC and are usually associated with inflammation and tumorigenesis [ 165 , 166 , 167 ]. Zhao et al, 2018, showed that CCL5 secreted by adipose tissue derived stem cells (ADSC) increases BC proliferation [ 168 ].…”
Section: Adipose Tissue As a Master Regulatormentioning
confidence: 99%